Reconsidering the Investment-Profit Nexus in Finance-Led Economies: an ARDL-Based Approach - Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2007)
A simple Post Keynesian growth model is developed, in which financial variables are explicitly taken into account. Different possible accumulation regimes are derived with respect to changes of these variables. Several variants of an investment function are estimated econometrically. The ARDL-based approach proposed by Pesaran et al. (2001) is argued to be superior for this purpose to the traditional cointegration approach. The econometric results are discussed with respect to a remarkable phenomenon that can be observed for some important OECD countries since the early 1980s: accumulation has generally been declining while profit rates have shown a tendency to rise. The author concentrates on one potential explanation of this phenomenon which is particularly relevant for the USA and relies on the hypothesis of a high propensity to consume out of capital income. The paper also gives an alternative explanation of the so-called "New Economy boom" in the USA at the end of the 1990s.
urn:nbn:de:101:1-20080814195
Keywords: C22; D14; E22; E25; G3; 330; Investment; Profitability; Financialisation; Time Series Econometrics.